2018
DOI: 10.3390/molecules23071736
|View full text |Cite
|
Sign up to set email alerts
|

Quick Multi-Class Determination of Residues of Antimicrobial Veterinary Drugs in Animal Muscle by LC-MS/MS

Abstract: On the basis of the highly sensitive and selective liquid chromatography-tandem mass spectrometry technique, a generic extraction solvent and a sample dilution method was developed for the residue analysis of different polar veterinary drugs known as fluoroquinolones, sulfonamides, macrolides, and tiamulin in chicken muscle. The results showed that the matrix-matched calibration curves of all 10 compounds were in an effective linear relationship (r2 ≥ 0.997) in the range of 0.2–100 μg L−1. At three spiking lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
4
1
1
Order By: Relevance
“…Compared with previous methods described above, our present work exhibited higher sensitivity and selectivity than the microbiologic analysis method and HPLC‐UV method, higher quantitative accuracy than the HPLC‐MS/MS with external standard quantification method, and UHPLC‐QTOF MS method. Zhang et al (2018) reported that strong matrix effect was observed for tiamulin analysis in chicken muscle; in contrast, no matrix effect was determined for TIF in plasma and various tissues (muscle, skin, liver, kidney, gill, and bile) in our study. In terms of LOD and LOQ, Dasenaki et al (2015) reported that LOD of tiamulin was 20 µg/kg in fish fillet with UHPLC‐QTOF MS method.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Compared with previous methods described above, our present work exhibited higher sensitivity and selectivity than the microbiologic analysis method and HPLC‐UV method, higher quantitative accuracy than the HPLC‐MS/MS with external standard quantification method, and UHPLC‐QTOF MS method. Zhang et al (2018) reported that strong matrix effect was observed for tiamulin analysis in chicken muscle; in contrast, no matrix effect was determined for TIF in plasma and various tissues (muscle, skin, liver, kidney, gill, and bile) in our study. In terms of LOD and LOQ, Dasenaki et al (2015) reported that LOD of tiamulin was 20 µg/kg in fish fillet with UHPLC‐QTOF MS method.…”
Section: Discussioncontrasting
confidence: 82%
“…To the best of our knowledge, several analytical methods have been reported to determine the tiamulin in biological matrices including microbiologic analysis method for determining of tiamulin in chicken, turkey poults, swine and dog blood (Laber, 1988; Laber & Schütze, 1977) and piglet serum (Riond et al, 1993), high‐performance liquid phase chromatography with ultraviolet detector (HPLC‐UV) method for tiamulin analysis in pork and chicken meat (Chen et al, 2006) and chicken plasma (Pomorska‐Mól & Kowalski, 2009), and HPLC‐MS/MS with external standard quantification method for monitoring tiamulin in chicken muscle (Zhang et al, 2018), liquid chromatography quadrupole time‐of‐flight mass spectrometry (UHPLC‐QTOF MS) for qualitative detecting tiamulin in gilthead sea bream ( Sparus aurata ) and sea bass ( Dicentrarchus labrax ) fillets (Dasenaki et al, 2015). Compared with previous methods described above, our present work exhibited higher sensitivity and selectivity than the microbiologic analysis method and HPLC‐UV method, higher quantitative accuracy than the HPLC‐MS/MS with external standard quantification method, and UHPLC‐QTOF MS method.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally in this process, there is a possibility that new metabolites as well as the parent compound of veterinary drugs are generated and exist. Because their chemical structure is similar to that of drugs for the human body, exposure to the human body may result in problems, such as the disturbance of body homeostasis, specific drug reactions, and the inhibition of therapeutic effects due to the introduction of unnecessary therapeutic agents [ 5 , 6 , 7 ]. Therefore, it is important to establish and comply with the maximum residue levels (MRLs) of drugs in agricultural production and to manage the residue levels of these toxic substances [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid chromatography (LC) has got a lot of benefits such as wide range detection and simultaneous quantitation of components based on their biological or chemical character [11]. Unit-mass resolution MS instruments does not provide enough selectivity in trace levels of residual antibiotics so that modern laboratories equipped by tandem Mass (MS/MS) capabilities to improve selectivity and consequently signal to noise ratio in their studied samples [11].…”
Section: Introductionmentioning
confidence: 99%